Faculty of Islamic Economics and Business Students’ Second Language Acquisition on Arabic through Hybrid and Receptive Learning Models - Putra, Wahyu Hanafi; Zaini, Hisyam; Holilulloh, Andi; Ahmed Shalabi, Essam Mustafa; Salma, Kunti Nadiyah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research aims to analyze the ability of students at the Faculty of Islamic Economics and Business (FEBI) IAIN Ponorogo to master Arabic as a second language through hybrid and sensory learning activities. This qualitative research with a case study type was done toward 176 students, with a sample of 20 students as the research population. The sampling technique was carried out using non-probability sampling with the snowball sampling method because the samples were taken based on the needs of this research. The research data is in the form of pronunciation of vocabulary sounds, spelling of Arabic letters, verbs and nouns, understanding the material being listened to, and reading Arabic texts of FEBI IAIN Ponorogo students in the odd semester of 2022/2023 academic year. The student reading source used in the research is the book "Al-'Arabiyyah fī Dirāsah al-Mu'āmalāt", namely the module book taught in the course "Arabic for Economics". Observation, interviews, and documentation are used to carry out data collection techniques. Data analysis techniques use data reduction, presentation, concluding, and verification. The results of the research show that the mastery of Arabic as a second language by students at the Islamic Economics and Business Faculty of IAIN Ponorogo in taking the "Arabic for Economics" course tends to be different from each other as they enter the preproduction stage of language acquisition. This means that they have not mastered much foreign vocabulary. This is caused by the educational background taken before college. Besides, another influencing factor is the neighbourhood where students live.